Clinical implications of microRNAs in cancer. (October 2013) - Bovell, LC; Putcha, BDK; Samuel, T; Manne, U
Abstract MicroRNAs (miRNAs) are endogenously produced non-coding RNAs that serve as micromanagers by negatively regulating gene expression. MiRNAs are implicated in several biological pathways including development of neoplasia. Because altered miRNA expression is implicated in the pathobiology of various cancers, these molecules serve as potential therapeutic targets. Using miRNA mimics to restore levels of aberrantly down-regulated miRNAs or miRNA inhibitors to inactivate over-expressed miRNAs shows promise as the next generation of therapeutic strategies. Manipulation of miRNAs offers an alternative therapeutic approach for chemo- and radiation-resistant tumors. Similarly, miRNA expression patterns can be used for diagnosis and to predict prognosis and efficacy of therapy. We present here an overview of how miRNAs affect cancers, how they may be used as biomarkers, and the clinical implications of miRNAs in cancer.